Reviewing and designing the operational processes and systems on clinical operations and activities for achieving higher efficiencies. - Malempati, Bhanuchand (2011)
The purpose of this dissertation is to understand the issues regarding the operational efficiencies, quality of service and use of IT systems and to provide recommendations to get better at the existing system. The work is primarily based in Nottingham University Hospital, associated with NHS-Trust, which currently is facing issues regarding Clinical Handover, Accountability, Missed-Results and use of IT systems. The root causes of the issues could be much wider and deeper than they appear. For understanding the current scenario, I got to know the systems and processes in place for various activities through observation and interaction with the staff. Also analysed the past data regarding the incidents in relation with these issues and had a detailed discussion with reviewers. Then, I conducted interviews with different people in the organization for finding the limitations and gaps in the process. This includes meeting people from different roles and different medical units within the organization. I also had discussions with the initiative teams on what has been done so far and what is planned for improving the processes. I collected inputs from the people and also gained feedback on the processes that they are personally involved in. The issues were then analyzed through literature review – both operational and health care literature, for getting better insight in to identifying the root causes. To gain a broader perspective on the best practices, conducted interviews with professionals from different sectors. This helped in understanding the advantages and identifying several activities that can be considered for incorporating at different phases of the existing process. Following the analysis, listed the suggestions for each matter of concern, highlighted the limitations that can impact the implementation process and discussed them with the staff members in higher roles. After gaining the feedback from staff members and their inputs on several aspects, drafted the recommendations for achieving higher efficiencies, better quality of the service and as a result, customer satisfaction.